A method for supporting the design of efficient heating systems using EU product policy data - Maria Calero-Pastor; Fabrice Mathieux; Daniel Brissaud; Jo Dewulf (International Journal of Sustainable Engineering, 2017)
The design of heating, ventilation and air conditioning systems is still a challenging engineering task which requires experienced and informed decision-making. These systems have a great energy-saving potential at the system level rather than at the level of the individual products of which they are composed. European environmental product policies have been very useful in facilitating a homogeneous rating scheme which can be used to compare the energy performance of different products that provide the same service. This paper proposes a simplified design method  which uses the performance of components that are regulated by European product policies to obtain the overall performance of heating systems in residential buildings. It is a flexible method and allows different product configurations to be assessed so as to optimise the system performance during the design phase. The method is tested on a real case study with domestic hot water and space heating systems. The case study shows the potential for improving the heating systems according to the performance levels of its products currently available in the market. Results of the domestic hot water system show that upgrading its storage tank to the maximum energy class (A+) could bring the highest energy savings ( 4162 kWh/y).